Zadania instytucji edukacji dla bezpieczeństwa na potrzeby bezpieczeństwa państwa - Martuszewska , Jolanta (Kultura-Społeczeństwo-Edukacja, 2020)
The desire to live a safe life is one of the most important human needs, while education is the basis of knowledge of the society as a whole. To ensure the safety of the individual and the security of the state, there is a need for stable cooperation between various security institutions. There are many safety education institutions that work for the needs of state security. These include the Education for Safety Bureau, the post of Education for Safety Inspector, the post of School Safety Coordinator, School Safety Clubs, etc. The aim of this paper is to describe the situation in education based on safety education teaching in the 21st century. Other objectives include indicating tasks and rational solutions in education on the basis of the principles introduced by scholars, such as J.A. Comenius, J. Locke, I. Kant, which remain valid to this day.